FROM PEC TO PEC24: A NEW REFERENCE CORPUS FOR ITALIAN (ItalianoLinguadue, 2025)
This article introduces the PEC24, an extension of the Perugia corpus, as a new reference corpus for Italian. The update mainly concerned the size of the corpus, which now consists of approximately 47 million tokens, with an addition of over 100,000 texts. The PEC24 maintains the same structure as its predecessor, divided into 10 sections, representing ten different written and spoken genres. In this article, after reviewing the spoken, written, and web corpora available for the Italian language, the internal composition of each section of the corpus will be described, followed by an explanation of how the corpus was annotated. Further, as the PEC24 is available and searchable online, examples of how it can be queried will be illustrated. In conclusion, the PEC24 represents a significant advancement in the panorama of Italian corpora, offering a representative and more comprehensive resource for linguistic research and corpus-bases studies. Dal PEC al PEC24: un nuovo corpus di riferimento per l’italianoQuesto articolo presenta un nuovo corpus di riferimento per l’italiano, il PEC24, un’estensione del Perugia Corpus. Il principale aggiornamento ha riguardato le dimensioni del corpus, che oggi conta circa 47 milioni di token, con l’aggiunta di oltre 100.000 testi. Il PEC24 mantiene la stessa struttura del suo predecessore, suddivisa in 10 sezioni che rappresentano dieci generi diversi di italiano scritto e parlato. Dopo una panoramica sui corpora di parlato, scritto e web disponibili per l’italiano, l’articolo descrive la composizione interna di ciascuna sezione del PEC24 e illustra il processo di annotazione. Inoltre, poiché il corpus è disponibile online e interrogabile, verranno mostrati alcuni esempi di interrogazione. In conclusione, il PEC24 rappresenta uno sviluppo significativo nel panorama dei corpora italiani, offrendo una risorsa più rappresentativa e articolata per la ricerca linguistica e gli studi basati sui corpora.